Factors Influencing Email Usage: Applying The UTAUT Model - Lim, Bee Lee (2005)
Email has now become an important thread that has been woven into the fabric of our daily communication in life. It is a powerful method of communication medium. To understand the effect, we must first comprehend the reason. Therefore, the study objective is to perform analysis on the possible factors which determined the acceptance of the electronic mail as communication media in organizations. The Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al., 2003) model was used as the basis of this study, and the data was collected using questionnaire. A total of 350 surveys were distributed to working adults in Penang, and a total of 138 useful responses were received, yielded 39.4 % response rate. The results of this study suggest that performance expectancy and social influences are important determinants of the behavioural intention to use email in an organizational environment.